A Copper Halide Promoted Regioselective Halogenation of Coumarins Using N-Halosuccinimide as Halide Source - Su, Jinling; Zhang, Yan; Chen, Mingren; Li, Weiming; Qin, Xuewei; Xie, Yanping; Qin, Lixiao; Huang, Shihua; Zhang, Min (Synlett, 2019)
A safe, convenient, and regioselective synthesis of 3-halo coumarins using a metal halide (CuX2 alone or with ZnX2) promoted halogenation with N-halosuccinimide (NXS) as halide source is reported. The synthesis involved the steady in situ generation of highly reactive positive halogen (X+) by the coordination of copper or zinc with the N-halosuccinimide and subsequent electrophilic aromatic substitution of the electron-deficient coumarins. This procedure works well also for the halogenation of less electron-rich naphthoquinones, flavones, and methoxypsoralen in moderate to quantitative yields. This protocol features simple experimental conditions using readily available inexpensive reagents and provides a convenient approach to the chlorination or bromination of some useful heteroaromatic compounds.
Keywords: coumarin; halogenation; aryl halide; electrophilic aromatic substitution; N-halosuccinimide